2023
DOI: 10.1111/ijfs.16511
|View full text |Cite
|
Sign up to set email alerts
|

Wet vacuum impregnation assisted in malting; its implication on steeping degree, germination energy and malt properties

Abstract: Summary The wet vacuum impregnation (WVI) was used in malting process to reduce soaking period. To implement WVI during steeping, vacuum pressure of 500 mmHg for 300 s, was applied twice on five Thai barley cultivars. The effect of WVI on germination energy, moisture content, phenolic acids, antioxidant activity (AOA) and malt quality were examined relative to Central European Commission for Brewing Analysis (MEBAK) malting condition. Moisture content in barley soaked by WVI and MEBAK steeping method were in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…However, steeping by WVI gave a higher content of free and bound phenolic acids, leading to a higher AOA. Studies have also shown that WVI does not limit barley germination and indicates the high potential of this technology in the malting process, as it reduces steeping time [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, steeping by WVI gave a higher content of free and bound phenolic acids, leading to a higher AOA. Studies have also shown that WVI does not limit barley germination and indicates the high potential of this technology in the malting process, as it reduces steeping time [12].…”
Section: Discussionmentioning
confidence: 99%
“…According to Gonu et al [12], wet vacuum impregnation (WVI) can be used in the malting process to reduce the soaking period. Grains of five Thai barley varieties were soaked at 500 mmHg for 300 s. The effects of WVI on germination energy, moisture content, phenolic acid content and antioxidant activity (AOA) were studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations